Easy access : the reference handbook for writers - Keene, Michael L.; Adams, Katherine H. (California : Mayfield, 1998)
Processes and products; Common writing problems; The basics from A to Z
Rev. ed. of: The easy access handbook, c1996
Includes index
Keywords: English language; Report writing; English language -- Rhetoric -- Handbooks, manuals, etc; English language -- Grammar -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc